2022
DOI: 10.2147/ccid.s395348
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Inhibitor Secukinumab Treatment in HIV-Positive Psoriasis Patient: A Case Report

Abstract: Psoriasis is an immune-mediated chronic inflammatory dermatosis influenced by hereditary and environmental factors. Human immunodeficiency virus (HIV) infection affects the immune system and exacerbates psoriatic lesions. We report the case of a 33-year-old male patient diagnosed with psoriasis vulgaris, psoriatic arthritis and HIV infection. Acitretin capsules, etanercept and high-active antiretroviral therapy (HAART) were effective. Two months after etanercept was discontinued, his condition worsened. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“… 16 , 17 Although data remain limited, regarding the use of biologics in the HIV population, existing evidence supports the therapeutic efficacy and safety of these agents, namely IL-23, IL-17 and tumour necrosis factor (TNF) inhibitors, for treating HIV-positive individuals with moderate-to-severe psoriasis. 18 20 Furthermore, evidence suggests that selective inhibition of IL-23, particularly through its unique p19 subunit, provides a more favourable safety profile when compared with inhibiting other inflammatory cytokines such as IL-17 and TNF. 17 In fact, a recent meta-analysis concluded that risankizumab has the most favourable long-term benefit–risk profile compared with other biologic agents for the treatment of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Although data remain limited, regarding the use of biologics in the HIV population, existing evidence supports the therapeutic efficacy and safety of these agents, namely IL-23, IL-17 and tumour necrosis factor (TNF) inhibitors, for treating HIV-positive individuals with moderate-to-severe psoriasis. 18 20 Furthermore, evidence suggests that selective inhibition of IL-23, particularly through its unique p19 subunit, provides a more favourable safety profile when compared with inhibiting other inflammatory cytokines such as IL-17 and TNF. 17 In fact, a recent meta-analysis concluded that risankizumab has the most favourable long-term benefit–risk profile compared with other biologic agents for the treatment of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…13 Conversely, the literature has documented successful treatment cases of psoriasis or psoriatic arthritis in individuals with HIV using IL-17 inhibitors. 14 The use of secukinumab therapy has shown potential effectiveness in our patient with juvenile psoriasis, psoriatic arthritis, and concurrent immunodeficiency. However, it is essential to exercise caution and conduct frequent and regular monitoring to evaluate disease activity and potential treatment side effects.…”
Section: Fu N D I N G I N Fo R M Ati O Nmentioning
confidence: 99%
“…No adverse events associated with immunosuppression or drug reactions were noted in these patients. [4][5][6][7][8][9] Wu et al 9 described the case of one such patient who was started on antiretroviral therapy and apremilast for the treatment of psoriasis. 9 However, due to lack of efficacy with apremilast, the patient was switched to secukinumab, resulting in complete resolution of lesions within 5 weeks.…”
Section: The Use Of Secukinumab In Patients With Chronic Infectionsmentioning
confidence: 99%